2017
DOI: 10.1007/10_2016_65
|View full text |Cite
|
Sign up to set email alerts
|

Vegetable Oil-Biorefinery

Abstract: Conventional vegetable oil mills are complex plants, processing oil, fruits, or seeds to vegetable fats and oils of high quality and predefined properties. Nearly all by-products are used. However, most of the high valuable plant substances occurring in oil fruits or seeds besides the oil are used only in low price applications (proteins as animal feeding material) or not at all (e.g., phenolics). This chapter describes the state-of-the-art of extraction and use of oilseed/oil fruit proteins and phyto-nutrient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 94 publications
0
2
0
Order By: Relevance
“…Vegetable oil fuels are derived from energy crops with high oil content and have become promising sustainable energy sources due to their degradability, convenient storage and transport, non-combustibility in an open flame, and low cost [122]. Research has shown that oilseed energy crops, such as sunflowers, are capable of producing oil [123], which can be reprocessed to obtain biodiesel, and the biodiesel is similar to petrochemical diesel but cleaner [124]. Biohydrogen is produced by anaerobic bacteria decomposing biomass in the presence of hydrogenase enzymes, reducing the amount of environmentally damaging methane produced [125].…”
Section: The Application Of Post-harvest Energy Crop Biomass Which Re...mentioning
confidence: 99%
“…Vegetable oil fuels are derived from energy crops with high oil content and have become promising sustainable energy sources due to their degradability, convenient storage and transport, non-combustibility in an open flame, and low cost [122]. Research has shown that oilseed energy crops, such as sunflowers, are capable of producing oil [123], which can be reprocessed to obtain biodiesel, and the biodiesel is similar to petrochemical diesel but cleaner [124]. Biohydrogen is produced by anaerobic bacteria decomposing biomass in the presence of hydrogenase enzymes, reducing the amount of environmentally damaging methane produced [125].…”
Section: The Application Of Post-harvest Energy Crop Biomass Which Re...mentioning
confidence: 99%
“…They consist of 95% triglycerides, with small amounts of mono-and diglycerides of higher fatty acids. The other ingredients are secondary, nontriglycerol compounds, such as phospholipids, sulfolipids, glycolipids, sphingolipids, waxes, polyphenols, phytosterols, hydrocarbons, vitamins, proteins, and pigments in the form of carotenoids and chlorophyll [31][32][33][34][35][36][37]. Among the oils of fish origin, shark liver oil and cod liver oil stand out.…”
Section: Introductionmentioning
confidence: 99%